A lithium iron phosphate carbon nanotube composite material and preparation method thereof
By wrapping carbon in the outer layer of lithium iron phosphate and loading it into a carbon nanotube composite material, the generation problem of carbon cladding rather than carbon nanotubes in the prior art is solved, and the high cycling performance and electrochemical performance of lithium batteries are achieved.
Patent Information
- Application Number
- CN202411777742.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-05
AI Technical Summary
Prior Art When preparing lithium iron phosphate-carbon nanotube composite materials, the high content of liquid carbon sources and insufficient contact with the catalyst lead to the formation of carbon cladding instead of carbon nanotubes, affecting the electrochemical performance of lithium iron phosphate.
The outer layer of lithium iron phosphate is used to wrap carbon and load it in the carbon nanotube composite material. The conductivity and stability of the carbon nanotube are improved through steps such as carboxylation and metal ion deposition.
It effectively improves the circulation and electrochemical properties of lithium batteries, enhances the conductivity and structural stability of the material, and reduces the degradation of the material.
Smart Images

Figure CN119240653B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a lithium iron phosphate carbon nanotube composite material and a preparation method thereof. Background Art
[0002] In order to improve the conductivity of lithium iron phosphate, the carbon coating method is currently widely used. On the one hand, it can improve the conductivity of lithium iron phosphate, and at the same time, it can prevent the growth of lithium iron phosphate grains under solid-phase high-temperature synthesis conditions, which is conducive to the preparation of nano-sized powders, thereby achieving high rates of lithium-ion batteries. Carbon nanotubes are a type of tube formed by rolling graphene sheets formed by carbon atoms. Due to their small diameter and large aspect ratio, carbon nanotubes are regarded as quasi-one-dimensional nanomaterials. It has been confirmed that carbon nanotubes have unique electrical properties and are a very good conductive agent that can be used in lithium battery positive electrode materials.
[0003] The patent application with publication number CN102427130 A discloses a lithium iron phosphate-carbon nanotube composite material, which is composed of lithium iron phosphate particles, nano-carbon layers outside the particles and carbon nanotubes, wherein the carbon nanotubes are in-situ grown in the nano-carbon layers during CVD. The prepared lithium iron phosphate precursor powder, catalyst and liquid carbon source are mixed evenly to form a slurry, which is fed into a high-temperature reactor by spray feeding to generate a lithium iron phosphate / carbon nanotube composite material, but the method of the application has the following problems: the liquid carbon source is convenient to spray into the reactor at a higher content, and the liquid carbon source is easy to generate a carbon coating layer instead of carbon nanotubes because it cannot fully contact with the catalyst, and the conductivity of carbon is far less than that of carbon nanotubes, thereby affecting the electrochemical performance of lithium iron phosphate; simply physically blending the lithium iron phosphate precursor powder, catalyst and liquid carbon source is difficult to achieve the effective coating of carbon or carbon nanotubes generated by the liquid carbon source on lithium iron phosphate, and carbon or carbon nanotubes may exist in a free form, and the exposed lithium iron phosphate affects the battery capacity and cyclability due to poor conductivity. Summary of the invention
[0004] The purpose of the present invention is to provide a lithium iron phosphate carbon nanotube composite material and a preparation method thereof. The lithium iron phosphate carbon nanotube composite material is used as a positive electrode material for a lithium battery and can effectively improve the cycle performance of the battery.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A lithium iron phosphate carbon nanotube composite material, comprising 90 to 95 parts of lithium iron phosphate and 1 to 5 parts of carbon nanotube composite material by weight;
[0007] The outer layer of the lithium iron phosphate is carbon-coated;
[0008] The carbon nanotube composite material comprises 3-4 parts of metal ions, 5-8 parts of cobalt and 80-85 parts of carbon nanotubes;
[0009] The inner diameter of the carbon nanotube is 8-12 nm, and the outer diameter is 10-15 nm.
[0010] A method for preparing a lithium iron phosphate carbon nanotube composite material comprises the following steps:
[0011] S1. Add LiOH·H2O and sodium dodecyl sulfate into deionized water, sonicate until completely dissolved, and add H3PO4 dropwise to obtain a mixed solution; dissolve FeSO4·7H2O and L-ascorbic acid in deionized water and slowly add the mixture dropwise to the mixed solution, stir evenly, perform hydrothermal reaction, cool, wash and dry to obtain lithium iron phosphate;
[0012] S2. Dispersing lithium iron phosphate and dopamine hydrochloride in tris(hydroxymethylaminomethane) buffer, stirring at room temperature, and washing to obtain polydopamine-coated lithium iron phosphate; dispersing the polydopamine-coated lithium iron phosphate and carbon nanotube composite material in anhydrous ethanol, grinding and stirring, drying, calcining, and cooling to obtain a lithium iron phosphate carbon nanotube composite material.
[0013] Furthermore, the molar ratio of LiOH·H2O, FeSO4·7H2O and H3PO4 is (3~3.3):(1~1.2):(1~1.2), the mass of L-ascorbic acid is 3%~8% of the mass of FeSO4·7H2O; the mass of sodium dodecyl sulfate is 3%~8% of the mass of FeSO4·7H2O; the dosage ratio of LiOH·H2O and deionized water in the mixed solution is 1g:20~30mL; the dosage ratio of FeSO4·7H2O and the total amount of deionized water is 1g:10~15mL.
[0014] Furthermore, the hydrothermal reaction conditions are 180-200° C. for 12-14 hours.
[0015] Furthermore, the dosage ratio of the lithium iron phosphate, dopamine hydrochloride and tris(hydroxymethyl)aminomethane buffer solution is (1-1.5) g: (100-200) mg: (50-60) mL, the pH value of the tris(hydroxymethyl)aminomethane buffer solution is 8-9, and the stirring time at room temperature is 6-8 h.
[0016] Furthermore, the drying condition is drying at 55-60° C. for 6-8 hours; the calcination condition is heating to 700-800° C. for 8-10 hours in an inert gas atmosphere, with a heating rate of 5-10° C. / min.
[0017] Furthermore, the carbon nanotube composite material is prepared by the following steps:
[0018] The carbon nanotubes are dispersed in a 65% nitric acid aqueous solution, heated and stirred, washed after cooling, dried, calcined and reduced with H2 to obtain carboxylated carbon nanotubes; the nitrate ethanol solution is slowly added to the carboxylated carbon nanotubes, immersed and washed to obtain a carbon nanotube material precursor; the carbon nanotube material precursor is added to ethylene glycol, mixed, and then a cobalt nitrate aqueous solution is slowly added, mixed, dried, calcined and reduced with H2 to obtain a carbon nanotube composite material.
[0019] Furthermore, the usage ratio of the carbon nanotubes, nitrates and cobalt nitrate is 1g: (500~800)mg: (500~800)mg; the usage ratio of the carbon nanotubes and 65% nitric acid aqueous solution is 1g: 50~60mL; the usage ratio of nitrates and anhydrous ethanol in the nitrate ethanol solution is (500~600)mg: (25~30)mL; the usage ratio of the carbon nanotube material precursor and ethylene glycol is 1g: 10~15mL.
[0020] Furthermore, the nitrate includes one or a combination of strontium nitrate, cerium nitrate, bismuth nitrate, platinum nitrate, nickel nitrate and palladium nitrate.
[0021] Furthermore, the heating and stirring is heating to 90-100°C and stirring for 16-18h; the impregnation time is 15-30min; the conditions for drying, calcining and reducing with H2 are drying at 50-60°C for 10-12h, calcining at 350-360°C for 2-3h, and reducing with H2 at 400-410°C for 2-3h.
[0022] Beneficial effects of the present invention:
[0023] (1) The present invention provides a lithium iron phosphate carbon nanotube composite material, which adopts a lithium iron phosphate outer layer wrapped with a layer of carbon and then loaded on the carbon nanotube composite material. After the carbon nanotube is carboxylated, the two ends of the carbon nanotube are opened, the inner surface area is increased, the surface tension of the ethanol solution is low, and the metal ions (including one or more combinations of strontium, cerium, bismuth, platinum, nickel, and palladium) are deposited inside the carbon nanotube, and under the action of the surfactant, cobalt is deposited on the outside of the carbon nanotube; the metal ions (including one or more combinations of strontium, cerium, bismuth, platinum, nickel, and palladium) introduced into the carbon nanotube improve the conductivity, thereby improving the electrochemical performance of the material, and at the same time play a supporting role for the carbon nanotube, preventing the carbon nanotube from collapsing during the reaction process, resulting in a decrease in the cyclability of the material; the introduction of cobalt into the carbon nanotube can not only improve the energy density of the battery, but also help stabilize the structure of the carbon nanotube and the positive electrode material, and reduce the degradation of the material.
[0024] (2) The polydopamine used in the present invention as a carbon source to coat the lithium iron phosphate avoids direct contact between the lithium iron phosphate and the electrolyte, thereby reducing the degradation of the material; at the same time, its strong adhesion enhances the compatibility between the carbon nanotube composite material and the lithium iron phosphate, which is beneficial for the adsorption and sintering of the carbon nanotube composite material on the lithium iron phosphate; the carbon coating layer and carbon nanotubes formed by polydopamine are beneficial to the penetration of the electrolyte and the exposure of the surface active sites, thereby enhancing the conductivity of the material.
[0025] (3) The sodium dodecyl sulfate used in the present invention as a surfactant can effectively reduce the average particle size of lithium iron phosphate particles and improve the battery specific capacity; the added L-ascorbic acid can effectively prevent the divalent iron from being oxidized in the air, reduce iron loss, and improve the electrochemical performance of lithium iron phosphate. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The present invention will be further described below in conjunction with the accompanying drawings.
[0027] Figure 1 is a SEM image of the lithium iron phosphate carbon nanotube composite material prepared in Example 1 of the present invention;
[0028] Figure 2 is a SEM image of the lithium iron phosphate carbon nanotube composite material prepared in Example 7 of the present invention;
[0029] Figure 3 is a SEM image of the lithium iron phosphate carbon nanotube composite material prepared in Comparative Example 1 of the present invention;
[0030] Figure 4 is a SEM image of the lithium iron phosphate carbon nanotube composite material prepared in Comparative Example 7 of the present invention;
[0031] Figure 5 It is a schematic diagram of the capacity residual rate of the lithium iron phosphate carbon nanotube composite material prepared in Examples 1, 4, 7, 9 of the present invention and Comparative Examples 1, 3, 5, 7 when cycled at 1C. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] This embodiment provides a lithium iron phosphate carbon nanotube composite material, which is prepared by the following steps:
[0035] S1. Add 12.6 g LiOH·H2O and 1.4 g sodium dodecyl sulfate to 300 mL deionized water, sonicate until completely dissolved, and add 9.8 g H3PO4 dropwise to obtain a mixed solution; dissolve 27.8 g FeSO4·7H2O and 1.4 g L-ascorbic acid in 100 mL deionized water and slowly add the mixture dropwise to the mixed solution, stir evenly, perform hydrothermal reaction, react at 200° C. for 12 h, cool, wash, and dry to obtain lithium iron phosphate;
[0036] S2, 1g of carbon nanotubes (with an inner diameter of 8nm and an outer diameter of 12nm) were dispersed in 50mL of a 65% nitric acid aqueous solution, heated to 90°C and stirred for 16h, washed after cooling to room temperature, dried at 60°C for 10h, calcined at 350°C for 3h, and reduced with H2 at 400°C for 2h to obtain carboxylated carbon nanotubes; 600mg of strontium nitrate was dissolved in 25mL of ethanol solution and slowly added to the carboxylated carbon nanotubes, immersed for 20min and washed to obtain a carbon nanotube material precursor; 1g of the carbon nanotube material precursor was added to 10mL of ethylene glycol, mixed, and then 12mL of a 50mg / mL cobalt nitrate aqueous solution was slowly added dropwise, mixed, dried at 60°C for 10h, calcined at 350°C for 3h, and reduced with H2 at 400°C for 2h to obtain a carbon nanotube composite material;
[0037] S3. Disperse 1 g of lithium iron phosphate and 150 mg of dopamine hydrochloride in 50 mL of tris(hydroxymethylaminomethane) buffer (pH=8), stir at room temperature for 8 h, and wash to obtain polydopamine-coated lithium iron phosphate; disperse 0.94 g of polydopamine-coated lithium iron phosphate and 0.04 g of carbon nanotube composite material in anhydrous ethanol, grind and stir, dry at 60°C for 6 h, heat to 700°C in an inert gas atmosphere and calcine for 8 h at a heating rate of 10°C / min, and cool to obtain a lithium iron phosphate carbon nanotube composite material.
[0038] The SEM image of the prepared lithium iron phosphate carbon nanotube composite material is as follows: Figure 1 As shown, the size is uniform; the capacity remaining rate of the lithium iron phosphate carbon nanotube composite material cycled at 1C is as follows Figure 5 As shown, it shows good recyclability.
[0039] Example 2
[0040] The present embodiment is different from the embodiment 1 in that "1.4 g sodium dodecyl sulfate" and "1.4 g L-ascorbic acid" in S1 are changed to "2.2 g sodium dodecyl sulfate" and "2.2 g L-ascorbic acid".
[0041] The remaining raw materials and preparation process remain the same as in Example 1.
[0042] Example 3
[0043] The present embodiment is different from the embodiment 1 in that "1.4 g sodium dodecyl sulfate" and "1.4 g L-ascorbic acid" in S1 are changed to "0.9 g sodium dodecyl sulfate" and "0.9 g L-ascorbic acid".
[0044] The remaining raw materials and preparation process remain the same as in Example 1.
[0045] Example 4
[0046] The present embodiment is different from the embodiment 1 in that the “600 mg strontium nitrate” and “12 mL of a 50 mg / mL aqueous cobalt nitrate solution” in S2 are replaced with “500 mg strontium nitrate” and “10 mL of a 50 mg / mL aqueous cobalt nitrate solution”.
[0047] The remaining raw materials and preparation process remain the same as in Example 1.
[0048] The capacity residual rate of the prepared lithium iron phosphate carbon nanotube composite material cycled at 1C is as follows: Figure 5 shown.
[0049] Example 5
[0050] The present embodiment is different from the embodiment 1 in that the “600 mg strontium nitrate” and “12 mL 50 mg / mL cobalt nitrate aqueous solution” in S2 are changed to “800 mg strontium nitrate” and “16 mL 50 mg / mL cobalt nitrate aqueous solution”.
[0051] The remaining raw materials and preparation process remain the same as in Example 1.
[0052] Example 6
[0053] The present embodiment is different from the embodiment 1 in that the “600 mg strontium nitrate” in S2 is changed to “628 mg cerium nitrate”.
[0054] The remaining raw materials and preparation process remain the same as in Example 1.
[0055] Example 7
[0056] The present embodiment is different from the embodiment 1 in that the “600 mg strontium nitrate” in S2 is changed to “300 mg strontium nitrate and 314 mg cerium nitrate”.
[0057] The remaining raw materials and preparation process remain the same as in Example 1.
[0058] The SEM image of the prepared lithium iron phosphate carbon nanotube composite material is as follows: Figure 2 As shown; the capacity remaining rate of lithium iron phosphate carbon nanotube composite material cycled at 1C is as follows Figure 5 shown.
[0059] Example 8
[0060] The present embodiment is different from the embodiment 1 in that "150 mg dopamine hydrochloride" in S3 is changed to "200 mg dopamine hydrochloride".
[0061] The remaining raw materials and preparation process remain the same as in Example 1.
[0062] Example 9
[0063] The difference between this embodiment and embodiment 1 is that "150 mg dopamine hydrochloride" in S3 is changed to "100 mg dopamine hydrochloride".
[0064] The remaining raw materials and preparation process remain the same as in Example 1.
[0065] The capacity residual rate of the prepared lithium iron phosphate carbon nanotube composite material cycled at 1C is as follows: Figure 5 shown.
[0066] Example 10
[0067] The difference between this comparative example and Example 1 is that in S3, "0.94 g of lithium iron phosphate coated with polydopamine and 0.04 g of carbon nanotube composite material" is changed to "0.92 g of lithium iron phosphate coated with polydopamine and 0.05 g of carbon nanotube composite material".
[0068] The remaining raw materials and preparation process remain the same as in Example 1.
[0069] Embodiment 11
[0070] The difference between this comparative example and Example 1 is that in S3, "0.94 g of lithium iron phosphate coated with polydopamine and 0.04 g of carbon nanotube composite material" is changed to "0.95 g of lithium iron phosphate coated with polydopamine and 0.02 g of carbon nanotube composite material".
[0071] The remaining raw materials and preparation process remain the same as in Example 1.
[0072] Comparative Example 1
[0073] The difference between this comparative example and Example 1 is that sodium lauryl sulfate is not added to S1.
[0074] The remaining raw materials and preparation process remain the same as in Example 1.
[0075] The SEM image of the prepared lithium iron phosphate carbon nanotube composite material is as follows: Figure 3 As shown; the capacity remaining rate of lithium iron phosphate carbon nanotube composite material cycled at 1C is as follows Figure 5As shown, sodium dodecyl sulfate, as a surfactant, when added during the preparation of lithium iron phosphate, will reduce the average particle size of lithium iron phosphate particles, increase the active sites of the material, and thus improve the recyclability.
[0076] Comparative Example 2
[0077] The difference between this comparative example and Example 1 is that L-ascorbic acid is not added to S1.
[0078] The remaining raw materials and preparation process remain the same as in Example 1.
[0079] Comparative Example 3
[0080] This comparative example is compared with Example 1, except that no strontium nitrate is added to S2, and the specific operation steps are as follows:
[0081] S2, 1g of carbon nanotubes (with an inner diameter of 8nm and an outer diameter of 12nm) were dispersed in 50mL of a 65% nitric acid aqueous solution, heated to 90°C and stirred for 16h, washed after cooling to room temperature, dried at 60°C for 10h, calcined at 350°C for 3h, and reduced with H2 at 400°C for 2h to obtain carboxylated carbon nanotubes; 1g of carboxylated carbon nanotubes were added to 10mL of ethylene glycol, mixed, and then 12mL of a 50mg / mL cobalt nitrate aqueous solution was slowly added dropwise, mixed, dried at 60°C for 10h, calcined at 350°C for 3h, and reduced with H2 at 400°C for 2h to obtain a carbon nanotube composite material;
[0082] The remaining raw materials and preparation process remain the same as in Example 1.
[0083] The capacity residual rate of the prepared lithium iron phosphate carbon nanotube composite material cycled at 1C is as follows: Figure 5 shown.
[0084] Comparative Example 4
[0085] This comparative example is compared with Example 1, except that cobalt nitrate is not added to S2, and the specific operation steps are as follows:
[0086] S2, 1g of carbon nanotubes (with an inner diameter of 8nm and an outer diameter of 12nm) were dispersed in 50mL of a 65% nitric acid aqueous solution, heated to 90°C and stirred for 16h, washed after cooling to room temperature, dried at 60°C for 10h, calcined at 350°C for 3h, and reduced with H2 at 400°C for 2h to obtain carboxylated carbon nanotubes; 600mg of strontium nitrate was dissolved in 25mL of ethanol solution and slowly added to the carboxylated carbon nanotubes, immersed for 20min and washed to obtain a carbon nanotube material precursor; dried at 60°C for 10h, calcined at 350°C for 3h, and reduced with H2 at 400°C for 2h to obtain a carbon nanotube composite material;
[0087] The remaining raw materials and preparation process remain the same as in Example 1.
[0088] Comparative Example 5
[0089] The difference between this comparative example and Example 1 is that no strontium nitrate and cobalt nitrate are added to S2, that is, carbon nanotubes are directly used. The specific operation steps are as follows:
[0090] S1. Add 12.6 g LiOH·H2O and 1.4 g sodium dodecyl sulfate to 300 mL deionized water, sonicate until completely dissolved, and add 9.8 g H3PO4 dropwise to obtain a mixed solution; dissolve 27.8 g FeSO4·7H2O and 1.4 g L-ascorbic acid in 100 mL deionized water and slowly add the mixture dropwise to the mixed solution, stir evenly, perform hydrothermal reaction, react at 200° C. for 12 h, cool, wash, and dry to obtain lithium iron phosphate;
[0091] S2. Disperse 1 g of lithium iron phosphate and 150 mg of dopamine hydrochloride in 50 mL of tris(hydroxymethylaminomethane) buffer (pH=8), stir at room temperature for 8 h, and wash to obtain polydopamine-coated lithium iron phosphate; disperse 0.94 g of polydopamine-coated lithium iron phosphate and 0.04 g of carbon nanotubes in anhydrous ethanol, grind and stir, dry at 60°C for 6 h, heat to 700°C in an inert gas atmosphere and calcine for 8 h at a heating rate of 10°C / min, and cool to obtain a lithium iron phosphate carbon nanotube composite material.
[0092] The remaining raw materials and preparation process remain the same as in Example 1.
[0093] The capacity residual rate of the prepared lithium iron phosphate carbon nanotube composite material cycled at 1C is as follows: Figure 5 shown.
[0094] Comparative Example 6
[0095] Compared with Example 1, this comparative example differs in that dopamine hydrochloride in S3 is replaced with glucose, and the specific implementation steps are as follows:
[0096] S3. Grind 1 g of lithium iron phosphate and 100 mg of glucose evenly, pre-calculate at 350°C for 1 h in an inert gas atmosphere to obtain carbon-coated lithium iron phosphate; disperse 0.94 g of carbon-coated lithium iron phosphate and 0.04 g of carbon nanotube composite material in anhydrous ethanol, grind and stir, dry at 60°C for 6 h, heat to 700°C for calcination at an inert gas atmosphere for 8 h, with a heating rate of 10°C / min, and obtain the lithium iron phosphate carbon nanotube composite material after cooling.
[0097] The remaining raw materials and preparation process remain the same as in Example 1.
[0098] Comparative Example 7
[0099] Compared with Example 1, the difference between this comparative example is that dopamine hydrochloride is not added in S3, and the specific implementation steps are as follows:
[0100] S3. Disperse 0.94 g of lithium iron phosphate and 0.04 g of carbon nanotube composite material in anhydrous ethanol, grind and stir, dry at 60°C for 6 h, heat to 700°C in an inert gas atmosphere and calcine for 8 h at a heating rate of 10°C / min, and obtain the lithium iron phosphate carbon nanotube composite material after cooling.
[0101] The remaining raw materials and preparation process remain the same as in Example 1.
[0102] The SEM image of the prepared lithium iron phosphate carbon nanotube composite material is as follows: Figure 4 As shown; the capacity remaining rate of lithium iron phosphate carbon nanotube composite material cycled at 1C is as follows Figure 5 As shown, polydopamine is used as a carbon source to coat lithium iron phosphate, which avoids direct contact between lithium iron phosphate and electrolyte, reduces the degradation of the material, and also makes the carbon nanotubes more dispersed, reduces agglomeration, and improves the cycle performance of the material.
[0103] The lithium iron phosphate carbon nanotube composite materials prepared in Examples 1 to 11 and Comparative Examples 1 to 7 were used as positive electrode active materials for button batteries to prepare button batteries. Capacity tests and cycle tests were performed on the prepared button batteries according to SJ / T 11797-2022. The test results are shown in Table 1:
[0104]
[0105] It can be seen from Table 1 that the lithium iron phosphate carbon nanotube composite material prepared in Example 1 has good discharge capacity and cycle performance as a positive electrode material; the difference between Examples 2 to 11 and Example 1 is only that the raw materials are adjusted within a reasonable range. From the test results, positive electrode materials with good electrochemical properties can be obtained.
[0106] Compared with Example 1, when Comparative Example 1 is combined with Examples 2 to 3, the discharge capacity and cycle performance of the material decrease after sodium dodecyl sulfate is not added. This is because sodium dodecyl sulfate is a surfactant. When added during the preparation of lithium iron phosphate, it will reduce the average particle size of the lithium iron phosphate particles and increase the battery specific capacity. However, adding too much will make the lithium iron phosphate too thin and reduce its electrochemical performance. Compared with Example 1, the added L-ascorbic acid in Comparative Example 2 can effectively prevent the divalent iron from being oxidized in the air, reduce the loss of divalent iron, and thus improve the battery capacity.
[0107] Compared with Example 1, Comparative Example 3 combined with Examples 4-5 reflects that the introduction of metal ions of nitrates inside carbon nanotubes helps prevent the carbon nanotubes from collapsing during the reaction, resulting in a decrease in the electrochemical performance of the material; Compared with Example 1, Comparative Example 4 combined with Examples 4-5 shows a decrease in the electrochemical performance of the battery, because cobalt can not only increase the energy density of the battery, but also help stabilize the structure of the carbon nanotubes and the positive electrode material, and reduce the degradation of the material; Compared with Example 1, Comparative Examples 3-5 combined with Examples 6-7 show that strontium nitrate can be reduced to a lower oxidation state compared to other nitrates, which affects the adhesion of the metal to the surface, allowing cobalt to be better dispersed outside the carbon nanotubes, thereby better improving the performance of the material.
[0108] Compared with Example 1, in Comparative Examples 6-7 combined with Examples 8-9, polydopamine is used as a carbon source to coat lithium iron phosphate, thereby avoiding direct contact between lithium iron phosphate and the electrolyte and reducing the degradation of the material; compared with other carbon sources (glucose), the strong adhesion of polydopamine enhances the compatibility of the carbon nanotube composite material and lithium iron phosphate, which is beneficial to the adsorption and sintering of the carbon nanotube composite material on the lithium iron phosphate; however, too much polydopamine will affect the charge and discharge reaction of the electrolyte and reduce the discharge capacity.
[0109] In summary, the present invention provides a lithium iron phosphate carbon nanotube composite material and a preparation method thereof. The prepared lithium iron phosphate carbon nanotube composite material is used as a positive electrode material for a lithium battery, has good discharge performance and cycle performance, and has good application prospects in the field of lithium battery materials.
[0110] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0111] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a lithium iron phosphate carbon nanotube composite material, characterized in that: The following steps are involved: S1. Add LiOH·H2O and sodium dodecyl sulfate into deionized water, sonicate until completely dissolved, and add H3PO4 dropwise to obtain a mixed solution; dissolve FeSO4·7H2O and L-ascorbic acid in deionized water and slowly add the mixture dropwise to the mixed solution, stir evenly, perform hydrothermal reaction, cool, wash and dry to obtain lithium iron phosphate; S2, dispersing lithium iron phosphate and dopamine hydrochloride in tris(hydroxymethylaminomethane) buffer, stirring at room temperature, and washing to obtain polydopamine-coated lithium iron phosphate; The polydopamine-coated lithium iron phosphate and carbon nanotube composite material is dispersed in anhydrous ethanol, ground and stirred, dried, calcined, and cooled to obtain a lithium iron phosphate carbon nanotube composite material; The carbon nanotube composite material is prepared by the following steps: The carbon nanotubes are dispersed in a 65% nitric acid aqueous solution, heated and stirred, washed after cooling, dried, calcined and reduced with H2 to obtain carboxylated carbon nanotubes; the nitrate ethanol solution is slowly added to the carboxylated carbon nanotubes, impregnated and washed to obtain a carbon nanotube material precursor; the carbon nanotube material precursor is added to ethylene glycol, mixed, and then the cobalt nitrate aqueous solution is slowly added, mixed, dried, calcined and reduced with H2 to obtain a carbon nanotube composite material; The nitrate includes one or a combination of strontium nitrate, cerium nitrate, bismuth nitrate, platinum nitrate, nickel nitrate and palladium nitrate.
2. The method for preparing a lithium iron phosphate carbon nanotube composite material according to claim 1, characterized in that: The inner diameter of the carbon nanotube is 8-12 nm, and the outer diameter is 10-15 nm.
3. The method for preparing a lithium iron phosphate carbon nanotube composite material according to claim 1, characterized in that: The molar ratio of LiOH·H2O, FeSO4·7H2O and H3PO4 is (3~3.3):(1~1.2):(1~1.2), the mass of L-ascorbic acid is 3%~8% of the mass of FeSO4·7H2O; the mass of sodium dodecyl sulfate is 3%~8% of the mass of FeSO4·7H2O; the dosage ratio of LiOH·H2O and deionized water in the mixed solution is 1g:20~30mL; the dosage ratio of FeSO4·7H2O and the total amount of deionized water is 1g:10~15mL.
4. The method for preparing a lithium iron phosphate carbon nanotube composite material according to claim 1, characterized in that: The hydrothermal reaction conditions are 180-200° C. for 12-14 hours.
5. The method for preparing a lithium iron phosphate carbon nanotube composite material according to claim 1, characterized in that: The dosage ratio of the lithium iron phosphate, dopamine hydrochloride and tris(hydroxymethyl)aminomethane buffer solution is (1-1.5) g: (100-200) mg: (50-60) mL, the pH value of the tris(hydroxymethyl)aminomethane buffer solution is 8-9, and the stirring time at room temperature is 6-8 hours.
6. The method for preparing a lithium iron phosphate carbon nanotube composite material according to claim 1, characterized in that: The drying condition is to dry at 55-60° C. for 6-8 hours; the calcination condition is to heat to 700-800° C. for 8-10 hours in an inert gas atmosphere, with a heating rate of 5-10° C. / min.
7. The method for preparing a lithium iron phosphate carbon nanotube composite material according to claim 1, characterized in that: The usage ratio of the carbon nanotubes, nitrates and cobalt nitrate is 1g:(500-800)mg:(500-800)mg; the usage ratio of the carbon nanotubes and 65% nitric acid aqueous solution is 1g:50-60mL; the usage ratio of nitrates and anhydrous ethanol in the nitrate ethanol solution is (500-600)mg:(25-30)mL; the usage ratio of the carbon nanotube material precursor and ethylene glycol is 1g:10-15mL.
8. The method for preparing a lithium iron phosphate carbon nanotube composite material according to claim 1, characterized in that: The heating and stirring is heating to 90-100°C and stirring for 16-18h; the impregnation time is 15-30min; the conditions for drying, calcining and reducing with H2 are drying at 50-60°C for 10-12h, calcining at 350-360°C for 2-3h, and reducing with H2 at 400-410°C for 2-3h.
9. A lithium iron phosphate carbon nanotube composite material, characterized in that: The composite material is prepared by the method for preparing the lithium iron phosphate carbon nanotube composite material according to any one of claims 1 to 8.
Citation Information
Patent Citations
Lithium iron phosphate-carbon nanotube composite material, preparation method, and application thereof
CN102427130A
Carbon nanotube key joint lithium iron phosphate composite electrode material and preparation method thereof
CN101442126A
Polydopamine / carbon nanotube <at>cobalt nickel oxide composite material and preparation method and application thereof
CN108987119A